A novel necroptosis-related gene signature predicts the prognosis and immunotherapeutic response in breast cancer through immune infiltration - Dezhi Lu; Sifang Qiu; Zhiqiang Zeng (Discover Oncology)
Abstract Growing evidence has demonstrated the association between necroptosis and tumorigenesis and immunotherapy. However, the influence of overall necroptosis related genes on prognosis and immune microenvironment of breast cancer is still unclear. In this study, We systematically analyzed the necroptosis related gene patterns and tumor microenvironment characteristics of 1294 breast cancer patients by clustering the gene expression of 22 necroptosis related genes. Three breast cancer subtypes that had different necroptosis patterns and distinct tumor microenvironment characteristics were recognized. The NecroptosisCluster B was featured by favorable prognosis, activated immune molecules and higher scores of immune cells. The NecroptosisScore was constructed to quantitatively evaluate the necroptosis level of individual patients. High NecroptosisScore were characterized by elevated expression levels of MHC molecules, stimulated infiltration of immune cells and lengthened survival. High NecroptosisScore were correlated with lower tumor mutation burden (TMB), and higher PD-1/CTLA4 expression. Surprisingly, patients with high NecroptosisScore exhibited better benefits in immunotherapy. This study highlighted that necroptosis was correlated with several aspects of breast cancer and affected the immune function. Further understanding of necroptosis will support our insight into the tumor immune landscape of breast cancer and facilitate the development of more effective treatment strategies.